Halal alternative raw materials for pharmaceutical and cosmetic applications: a systematic review - Deliaz, Mochamad Fajar; Kurniawan, Akbar Rizqi; Sari, Feni Mustika; Setiadi, Feri (Universitas Airlangga, 2025)
The global pharmaceutical and cosmetic industries continue to grow, driven by innovations that emphasize product quality and effectiveness. However, the halal status of raw materials has become a critical concern, especially with the increasing number of Muslim consumers worldwide. Conventional ingredients such as gelatin, collagen, and keratin are often derived from pigs or animals not slaughtered according to Islamic law, raising religious, ethical, health, and sustainability issues. This study systematically reviews halal alternative raw materials for pharmaceutical and cosmetic applications. Literature searches were conducted through databases such as Google Scholar, ScienceDirect, and DOAJ, focusing on articles published between 2018 and 2025 that met specific inclusion and exclusion criteria. The review identifies four main categories of halal alternatives: halal animal-based sources, including fish skin, bones, and marine animals; plant-based sources, such as agar, carrageenan, pectin, starch–alginate, and natural colorants; microbial sources, including xanthan gum and non-animal-derived chitosan; and synthetic/recombinant sources, such as recombinant collagen, recombinant insulin, and synthetic polymers. These materials serve diverse functions in pharmaceutical and cosmetic formulations, including capsule coatings, tablet coatings, emulsifiers, stabilizers, colorants, and drug delivery systems. Each alternative presents unique advantages and challenges in terms of formulation stability, bioactivity, production cost, and consumer acceptance. In conclusion, halal alternative raw materials have strong potential to replace conventional non-halal ingredients and support the global trends of clean beauty, sustainability, and ethical consumerism; however, further research is required to optimize technology and strengthen regulatory frameworks Keywords: Alternative Gelatin, Halal Cosmetic, Halal Ingredients, Halal Pharmaceutical, Sustainable Logistics